Extracorporeal reconstruction of the radial head - Kow, Ren Yi; Mustapha@Zakaria, Zaharul Azri; Jaya Kumar, Ruben; Low, Chooi Leng; Siron @ Baharom, Khairul Nizam (Universiti Malaysia Sabah, 2021)
Radial head fractures are common in adults. The radial head acts as an important stabilizer of the radius, especially during the forearm pronation and supination. Surgical treatment of Mason type III fracture of the radial head includes radial head excision, radial head replacement and open reduction and internal fixation. For patients treated with radial head excision, the radius might migrate proximally, causing complications such as chronic pain at the wrist, forearm, and elbow. On the other hand, radial head arthroplasty is associated with a high revision and removal rate. Hence, open reduction and internal fixation are preferred when feasible. This is technically demanding due to the severe displacement of the radial head fragments and limited surgical space. Mr K, a 30-year-old manual worker sustained a closed right radial head fracture Mason type III after an alleged fall. The radial head was displaced anteriorly. Intra-operatively, the radial headpieces were retrieved and were reconstructed extracorporeal and fixed with a miniplate. The patient subsequently recovered with good function. The new technique of extracorporeal reconstruction of the radial head offers a viable option to the surgeon with similar, or even better, outcomes in terms of elbow function.